Effects of Veratrum nigrum expansion on soil microbial community structure in inner Mongolian mountain steppe - Pang, Bo; Zhang, Hao; Liu, Tong; Yang, Dianlin; Wang, Hui; Zhang, Yanjun; Liu, Hongmei; Zhang, Haifang (Frontiers in Microbiology, 2025)
BackgroundsThe expansion of poisonous weeds can significantly affect soil microbial communities and their ecosystem functions. In this regard, the poisonous weed Veratrum nigrum has impacted vast regions of Inner Mongolia, with potential impacts on the microbial community structure. However, the mechanism associated with this change remain unclear.MethodsIn this study, we conducted a comparative analysis of four hazard levels (control CK, coverage = 0; light hazard L, coverage ≤20%; moderate hazard M, 20% < coverage ≤40%; and severe hazard S, coverage >40%) of V. nigrum in Inner Mongolia region, focusing on its effects on the soil physicochemical properties, microbial community structure, diversity, and co-occurrence patterns.ResultsResults revealed that expansion of V. nigrum significantly altered the physicochemical properties and structure of the soil microbiota. The contents of available nitrogen, total nitrogen, total phosphorus, available phosphorus, and available potassium in the S treatment were significantly higher than those in the CK (p < 0.05), indicating that the diffusion of V. nigrum enhanced nutrient availability. Compared with CK, the fungal Chao1 and Shannon diversity increased significantly in the S treatment, whereas the abundance of oligotrophs (Basidiomycota) decreased significantly. In contrast, the Chao1 and Shannon indices of bacteria under S treatment showed no significant difference compared to CK. Correlation analyses indicated that soil fungal community composition was more sensitive to the changes in soil physicochemical properties caused by V. nigrum than bacterial community composition. Additionally, microbial co-occurrence network analyses revealed that the expansion of V. nigrum led to an increase in competitive microbial interactions. Structural equation modeling confirmed the influence of V. nigrum expansion and nutrient changes on the fungal community composition and diversity.ConclusionThis study reveals that V. nigrum expansion enhances nutrient availability and promotes the recovery of soil microbial diversity in degraded grasslands, particularly soil fungi, indicating that V. nigrum expansion serves as a self-protective mechanism for degraded grasslands. Thus, we aimed to challenge the conventional perspective that poisonous weeds are invariably harmful and to offer new insights into their role within degraded grassland ecosystems.